Comparative study of the chemical composition of herb and flowers of Snapdragon (Antirrhinum majus l.) - Ilyina, Sofia; Zhuravel, Iryna (Annals of Mechnikov's Institute, 2024)
Herbal medicinal products play a crucial role in contemporary medicine. The search for new sources of biologically active compounds and the expansion of the range of phytopreparations are currently relevant. Snapdragons (Antirrhinum majus L.), a herbaceous plant belonging to the Plantain family (Plantaginaceae), present promising research prospects. In Ukraine, snapdragons are currently cultivated as ornamental plants, which provides a raw material base. The aim of this study was to conduct a comparative analysis of the chemical composition of the herb and flowers of snapdragons. Materials and Methods: the objects of the study were the herb and flowers of snapdragons (Antirrhini majus herba, Antirrhini majus flores) of the Overture and Snappy varieties. The raw materials were harvested during the flowering phase of the plants in August 2023 in the Kharkiv region (Ukraine). The chemical composition was studied using high-performance liquid chromatography. An accurate sample (approximately 1.0 g) of the raw material was placed in a ground-glass flask and 10 ml of 70% ethanol was added. The mixture was heated on a boiling water bath with a reflux condenser for 30 minutes. The extract was then cooled, filtered, and brought to volume with the same solvent in a 10 ml volumetric flask. Subsequently, 5 ml of the obtained extract was placed in a 10 ml volumetric flask and brought to volume with 70% ethanol. Chromatography was conducted on a Milichrom A-02 liquid chromatograph with a ProntoSil-120-5-C18 AQ column under the following conditions: length – 75 mm, diameter – 2 mm, with particle size – 5 μm. Eluent A consisted of 4 M lithium perchlorate and 0.1 M perchloric acid. Eluent B was acetonitrile. Detection was performed at 210, 220, 230, 240, 250, 260, 280, and 300 nm. The thermostat temperature was maintained at 40°C, and the mobile phase flow rate was 100 μl/min. The eluent gradient ranged from 5% to 100% eluent B over 40 minutes. Sample volumes were 800 μl (initial), 4000 μl, and 4300 μl. The obtained chromatograms were analyzed using the AlphaChrom software. Results: in the studied raw materials, 15 chemical compounds were identified, including sugars (glucose and fructose), free amino acids (phenylalanine, tryptophan), flavonoids (auronolin, quercetin-3-galactoside, quercetin-3-arabinofuranoside, quercetin-3-rhamnoside, apigenin 7,4′-diglucuronide, luteolin 7-glucuronide), carotenoids (lutein, ß-carotene), chalcononaringenin 4′-glucoside, cyanidin, and antirrhinoside. Significant qualitative differences between the herb and flowers, as well as between the Overture and Snappy varieties, were not detected. Therefore, for further research and the development of medicinal products, the use of raw materials from both studied varieties of garden snapdragons can be considered. Key words: Antirrhini majus herba, Snapdragons, high performance liquid chromatography (HPLC), flavonoids, iridoids, amino acids, sugars.